2017
DOI: 10.1002/2016jc011902
|View full text |Cite
|
Sign up to set email alerts
|

Role of wind in erosion‐accretion cycles on an estuarine mudflat

Abstract: Wind is an important regulator of coastal erosion and accretion processes that have significant ecological and engineering implications. Nevertheless, previous studies have mainly focused on storm‐generated changes in the bed level. This paper aims to improve the understanding of wind‐induced erosion‐accretion cycles on intertidal flats under normal (nonstormy) weather conditions using data that relates to the wave climate, near‐bed 3‐D flow velocity, suspended sediment concentration, and bed‐level changes on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Given that sediments on the Wanggang mudflat originate from the Yangtze River, the dry density used for this surface sediment (ρ dry ) was 1,300 kg/m 3 based on the recommendation of Yang et al (). M E is the erodibility parameter (m/Pa/s), and the applied value of M E in this study was 2.19 × 10 −6 m/Pa/s, which is applicable for the neighboring intertidal mudflat at the Yangtze delta front based on Shi et al (), and is also of the same order of magnitude as a large number of published results (e.g., Shi et al, ; Winterwerp & van Kesteren, ). τ ce is the critical shear stress for the erosion of bottom sediments (N/m 2 ).…”
Section: Methodsmentioning
confidence: 51%
See 1 more Smart Citation
“…Given that sediments on the Wanggang mudflat originate from the Yangtze River, the dry density used for this surface sediment (ρ dry ) was 1,300 kg/m 3 based on the recommendation of Yang et al (). M E is the erodibility parameter (m/Pa/s), and the applied value of M E in this study was 2.19 × 10 −6 m/Pa/s, which is applicable for the neighboring intertidal mudflat at the Yangtze delta front based on Shi et al (), and is also of the same order of magnitude as a large number of published results (e.g., Shi et al, ; Winterwerp & van Kesteren, ). τ ce is the critical shear stress for the erosion of bottom sediments (N/m 2 ).…”
Section: Methodsmentioning
confidence: 51%
“…There are many uncertainties in measurements of bed‐level changes in a highly turbid estuarine environment (e.g., Miao, 2016; Shi et al, ). The first reason for this is the universal presence of a fluid‐like mud layer due to the effect of high SSCs on intertidal flats (e.g., Andersen et al, ; Yang et al, , 2005; Shi et al, ). This is supported by observations on another mudflat in the Yangtze delta front, where >10 kg/m 3 of near‐bed SSC can be generally observed, even during normal weather (Miao, ; Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Observational (Andersen et al, ; Christiansen et al, ; Deloffre et al, , ; Fan et al, ; Marion et al, ; Shi et al, ; Wang et al, ; Yang et al, , ) and modeling (Fagherazzi et al, ; Hu et al, ; Maan et al, ; Roberts et al, ) studies have both revealed that waves have important impacts on the morphology and sediment grain size of tidal flats. So future research should couple the effects of cross‐shore and alongshore tidal currents including waves.…”
Section: Discussionmentioning
confidence: 99%
“…Observational (Andersen et al, 2006;Christiansen et al, 2006;Deloffre et al, 2005Deloffre et al, , 2007Fan et al, 2006;Marion et al, 2009;Shi et al, 2017;Wang et al, 2009;Yang et al, 2003Yang et al, , 2008 Here we only considered one mud fraction and one sand fraction in the models. In fact, both sand and mud can be divided into more fractions of different properties.…”
Section: Future Workmentioning
confidence: 99%
“…Many studies have focused on wind effects on morphodynamic processes on intertidal flats (Friedrichs 1995;Fagherazzi et al 2007;Fagherazzi and Wiberg 2009;Mariotti and Fagherazzi 2013;Hunt et al 2017;Shi et al 2017). These studies emphasize the importance of wind-wave effects on estuarine morphodynamics; mechanisms of wave-induced sedimentary processes are already well described (Green and Coco 2014).…”
Section: Introductionmentioning
confidence: 99%